EFEKTIVITAS KEGIATAN PENYULUHAN PERIKANAN TERHADAP KEPUASAN POKDAKAN DI KECAMATAN BALEENDAH KABUPATEN BANDUNG, JAWA BARAT - Apriliani, Izza Mahdiana; Shafa, Bellarisa Rahma; Haryadi, Ikhsan (Universitas Gorontalo, 2024)
Cultivator satisfaction is an important thing in the implementation of fisheries extension activities. In this case, the satisfaction of farmers is related to the quality of fisheries extension services carried out. The purpose of this observation is to determine the level of satisfaction of farmers with aquaculture extension activities and the development of fish farming group (pokdakan) with extension activities in Baleendah District. Data collection methods in the form of interviews, questionnaires, observations and documentation as well as data analysis used are descriptive analysis and scoring using the Likert scale. Cultivatorâ€™s characteristics based on gender is more dominant male with a percentage of 93.3%, the age of cultivators is more dominant age 34- 45 with a percentage of 73.33%, the education level of cultivators is more dominant in elementary school (SD) with a percentage of 53.33%, and the area of cultivated land is more dominant by 5-100 with a percentage of 53.33%. The level of satisfaction of cultivators with extension activities in Baleendah District, Bandung Regency can be said to be satisfied. This can be seen from the average score of each indicator, namely ð‘š2tangible 4.11 with a description of satisfied, reliability 4.02 with a description of satisfied, responsiveness 4.02 with a description of satisfied, assurance 4.02 with a description of satisfied, and empathy 3.97 with a description of satisfied so that the average of all dimensions used to measure the level of satisfaction of cultivators in Baleendah District, Bandung Regency is with 4.03 which shows that the cultivators are satisfied with the services and extension activities received. Cultivators think that extension activities can help from the aspects of capital, facilities, information, and technology.